2009
DOI: 10.1126/scisignal.293re8
|View full text |Cite
|
Sign up to set email alerts
|

G Protein–Coupled Receptors, Cholinergic Dysfunction, and Aβ Toxicity in Alzheimer’s Disease

Abstract: The beta-amyloid (Abeta) peptide is associated with the pathogenesis of Alzheimer's disease (AD). Evidence gathered over the last two decades suggests that the gradual accumulation of soluble and insoluble Abeta peptide species triggers a cascade of events that leads to the clinical manifestation of AD. Abeta accumulation has also been associated with the cholinergic dysfunction observed in AD, which is characterized by diminished acetylcholine release and impaired coupling of the muscarinic acetylcholine rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 101 publications
1
42
0
1
Order By: Relevance
“…The Ab42 accumulation associated with the cholinergic dysfunction observed in AD is characterised by diminished acetylcholine release and impaired coupling of the muscarinic acetylcholine receptors with heterotrimeric GTPbinding proteins (G proteins). In an AD transgenic mouse model, it has been shown that abnormal processing of these G proteins alters Tau phosphorylation, leading to neurodegeneration and neuronal loss (Thathiah and De Strooper 2009). Our data seem to suggest that similar interactions, occurring between Ab42 accumulation and Tau phosphorylation, could explain why in the current study SLAI impairment was associated with both Ab42 and p-Tau CSF levels (Haense et al 2010).…”
Section: Discussionsupporting
confidence: 46%
“…The Ab42 accumulation associated with the cholinergic dysfunction observed in AD is characterised by diminished acetylcholine release and impaired coupling of the muscarinic acetylcholine receptors with heterotrimeric GTPbinding proteins (G proteins). In an AD transgenic mouse model, it has been shown that abnormal processing of these G proteins alters Tau phosphorylation, leading to neurodegeneration and neuronal loss (Thathiah and De Strooper 2009). Our data seem to suggest that similar interactions, occurring between Ab42 accumulation and Tau phosphorylation, could explain why in the current study SLAI impairment was associated with both Ab42 and p-Tau CSF levels (Haense et al 2010).…”
Section: Discussionsupporting
confidence: 46%
“…Interactions with the insulin receptor 52 , effects on hypoxia-induced factor HIF-1 (ref. 53), clustering of the G protein-coupled angiotensin type 2 receptor and other mechanisms have also been described 54 . Recently, the cellular prion protein PrP c emerged as a specific receptor for toxic Aβ oligomers 55 , which also has resulted in considerable controversy.…”
Section: An Alternative Interpretation Of Ab Oligomer Toxicitymentioning
confidence: 97%
“…these GPCRs. 10 However, the mechanisms by which they activate α-secretases are not always well understood.…”
mentioning
confidence: 99%